2020
DOI: 10.1590/1980-5918.033.ar02
|View full text |Cite
|
Sign up to set email alerts
|

Training with elastic and conventional devices on body composition: systematic review and meta-analysis

Abstract: Licensed under a Creative Commons attributionTraining with elastic and conventional devices on body composition: systematic review and meta-analysis Treinamento em dispositivos elásticos e convencionais sobre a composição corporal: revisão sistemática e meta-análise Entrenamiento en dispositivos elásticos y convencionales sobre composición corporal: revisión sistemática y metaanálisis Abstract Introduction: Given the practicality and low cost of elastic devices, a comparison with conventional devices may be ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Previous results confirmed the effectiveness of traditional resistance training in improving fluids component distribution in older women (dos Dos Santos et al, 2016;Souza et al, 2017). In contrast, the studies that have assessed the changes in fat-free mass failed to report the changes in intracellular and extracellular water (Lopes et al, 2020;Ramos et al, 2014), therefore so a direct comparison cannot be made. However, the present results showed that resistance training with elastic tubes is not sufficient enough to induce any change.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous results confirmed the effectiveness of traditional resistance training in improving fluids component distribution in older women (dos Dos Santos et al, 2016;Souza et al, 2017). In contrast, the studies that have assessed the changes in fat-free mass failed to report the changes in intracellular and extracellular water (Lopes et al, 2020;Ramos et al, 2014), therefore so a direct comparison cannot be made. However, the present results showed that resistance training with elastic tubes is not sufficient enough to induce any change.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 88%
“…Bioimpedance-based predictive equations allows for monitoring changes in i) fat mass, ii) body fluids, including those that contribute to forming the body cell mass representing the metabolically J o u r n a l P r e -p r o o f Journal Pre-proof and elastic resistance training (Lopes et al, 2019), the changes in body composition after a resistance training program with elastic tubes are still unclear (Lopes et al, 2020). In this regard, the few studies available in older populations have shown contrasting results, reporting improvements (Liao et al, 2018) or absence of variation (Ramos et al, 2014) in body composition parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used [18,19]. This review was registered in the International Prospective Register of Systematic Reviews (PROS-PERO).…”
Section: Methodsmentioning
confidence: 99%
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used. 16,17 This review was registered in the International Prospective Register of Systematic Reviews (PROSPERO). We analyzed a total of 13,497 studies retrieved from different databases and one study retrieved from the reference list of another study.…”
Section: Methodsmentioning
confidence: 99%